PERAN GURU DALAM MEMBENTUK KARAKTER PERCAYA DIRI PESERTA DIDIK DI SD IES AL-GHUROBA KABUPATEN SORONG - Oki Sandra Agnesa; Indah Puspita Sari; Darnanengsih Darnanengsih (MISOOL: Jurnal Pendidikan Dasar, 2021)
This thesis discusses the role of teachers in shaping self-confidence in SD IES Al-Ghuroba, Sorong Regency. Overcoming the collapse of the character is to eliminate or improve the factors that cause it. There are five areas of education that can foster good character, namely: family, self, school, environment, and society. The development of national character is a collective commitment of the Indonesian people to face today's global demands. This study aims to determine the efforts of teachers in shaping the confident character of students and also the obstacles faced by teachers in shaping the confident character of students and their solutions. To achieve the above objectives, the type of research used in this research is qualitative research. Based on the results of direct observations and interviews between researchers and principals, teachers, and students at SD IES Al-Ghuroba. The results of the study indicate the efforts made by the teacher namely: giving motivation to students, giving praise or gifts, and often presenting them in front of their friends in turn in class. The obstacles faced by teachers in increasing the confidence of students are the mindset of students who are different and there are still some students who lack self-confidence. Therefore, the solution taken by the teacher as an educator is to try as much as possible to guide and provide strong motivation and encouragement to students so that they have self-confidence